اضطرابات الأظافر عند مرضى الطب الداخلي: الانتشار والدور الممكن في التشخيص - دلول, محمود (Latakia University Journal -Medical Sciences Series, 2019)
تستخدم اضطرابات الأظافر بشكل تقليدي في المساعدة في التشخيص. ولكن فائدتها مع ذلك غير معروفة بشكل عام وكذلك قيمتها التنبئية بشكل خاص. كان هدفنا من هذه الدراسة مسح تبدلات الأظافر وتوضيح أهمية تبدلات الأظافر في تشخيص الأمراض الداخلية. تم فحص أظافر اليدين عند 592 مريضاً تم قبولهم في قسم الأمراض الداخلية في مشفى الأسد الجامعي في اللاذقية. تم حساب نسب الانتشار على أساس توزيع ثنائي الحد. أكثر الموجودات شيوعاً كانت غياب الهليل (25.9%[22.5-29.5])، الأظافر البيضاء (16.1% [13.0-19.1])، تكسر الأظافر (8.5% [7.5-9.1]. شوهدت الترافقات الهامة التالية: المرض الرئوي والتعجر (النسبة الترجيحية [OR]=4.2، مجال الثقة 95%[CI]=1.6-9.8)، المرض الدموي وتكسر الأظافر (OR = 4.6، 95%CI = 1.6-13.7)، المرض الدموي وأظافر تيري (OR = 8.4، 95%CI = 2.6-26.2)، والمرض المعدي المعوي والأظافر الكلابية (OR = 32.4، 95%CI = 3.9-304.4). تم تحديد بضعة ترافقات هامة، مما يشير إلى أن اضطرابات الأظافر قد تكون مفتاح التشخيص في الأمراض الداخلية المزمنة. قلما وصف الترافق بين المرض المعدي المعوي والأظافر الكلابية في السابق. Nail changes have traditionally been used as diagnostic aids. Their usefulness in general and predictive value in particular, however, is not known. Our purpose was to survey nail changes and to clarify the potential of nail abnormalities to diagnose internal diseases. The fingernails of 592 patients admitted to internal medicine in Al-Aasad University Hospital in Lattakia were examined. The point prevalence rates were calculated on the basis of binomial distribution. The most common finding were absence of lunulae (25.9% [22.5% to 29.5%]), white nails (16.1% [13.0% to 19.1%]), and brittle nails (8.3% [7.5% to 9.1%]). The following significant associations were noted: pulmonary disease and clubbing (odds ratio [OR] = 4.2, 95% confidence interval [CI] = 1.6 to 9.8), hematologic disease and brittle nails (OR = 4.6, 95%CI = 1.6 to 13.7), hematologic disease and Terry nails (OR = 8.4, 95%CI = 2.6 to 26.2),gastrointestinal disease and pincer nails (OR = 32.4, 95%CI = 3.9 to 304.4). Several significant associations were identified, suggesting that nail abnormalities can be diagnostic clues in the diagnosis of chronic internal diseases. An association between pincer nails and gastrointestinal disease has been rarely described.